Lateralidad en el desarrollo de la lectoescritura en los estudiantes de la Unidad Educativa Fiscomisional “San Vicente de Paúl - Donoso Lara, Andrea Fernanda (2024)
This research aimed to analyze the laterality in reading and writing development in 4th grade Basic School students in the Fiscomisional Educational Unit "San Vicente de Paul," period 2023 - 2024. Laterality determines the dominance of one of the cerebral hemispheres, whether the child is right-handed or left-handed, which is fundamental in learning to read and write. Reading and writing develop divergent thinking in children, thus making them look for different alternatives in certain situations. Correct laterality from an early age will have positive results in learning to read and write. The methodology used has a quantitative approach; its design is non-experimental due to its level or scope; it is descriptive due to the primary objectives; the place is field, and the time is transversal. The study population was the students of the Fiscal Educational Unit "San Vicente de Paul," and the non-probabilistic and intentional sample was the students of 4th grade; Students whose parents signed the informed consent were considered. The technique used was psychometric; the instruments for data collection were the Reading and Writing Analysis Test "TALE" and the "HARRIS" lateral dominance test. For the analysis of the information and the interpretation of the data, the techniques suggested by the approach were used according to the instrument applied. For the processing of the data, objectivity was used with the Excel program, complemented with the elaboration of graphical representation statistics such as: tables and diagrams, of the analysis of each test reflected in the test, thus the results obtained globally according to the participation of the students. Based on the results, it was concluded that laterality is not just a theoretical concept, but it has practical implications for the reading and writing process in children in 4th grade. Problems in school performance, especially in children who do not have a well-defined laterality, can be addressed through early identification and intervention.